Management of an Elderly Patient Via Trans-Catheter Approach for a Post-Cardiac Surgery Aortic Pseudoaneurysm: A Case Report - Sadiq, Nadeem; Iqbal, Afsheen; Sami, Ashar; Maqsood, Sarah; Kamal, Dawood; Masroor, Rehan; Younas, Umair; Akhtar, Khurram; Javaid, Rehana; Sana, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Pseudoaneurysm of the ascending aorta is a rare but dreadful complication following cardiac surgery and it has more chances of rupturing in elderly females. It occurs as a result of lengthy cardiopulmonary bypass time and associated degenerative changes in old patients. Due to the poor prognosis, early diagnosis and management of this complication is essential. Our case is of a 68-year old female who developed a 44 mm large ascending aortic pseudoaneurysm 7 days after undergoing (coronary artery bypass grafting) CABG for long-standing. (Triple vessel coronary artery disease) TVCAD. The location of the pseudoaneurysm was found to be just above the vein graft to the RCA on (computerized tomography) CT-Aortogram. 2D-Echocardiography showed an Ejection Fraction of 45% and a 22 mm neck of the aneurysmal sac. Trans-catheter device closure was planned and the neck was successfully closed with no residual leak seen on (computerized tomography) CT-Aortogram performed after 3 days. However, she developed cardiac arrest during the device closure and even after successful resuscitation she went into a state of septic shock in the following weeks that did not respond to maximum medical treatment which unfortunately led to her death. A review of 3 similar cases of post-cardiac surgery aortic pseudoaneurysms which were successfully managed via trans-catheter device closure is also discussed. Early diagnosis and interventional treatment of post-cardiac surgery aortic pseudoaneurysms in elderly patients is necessary alongside very careful surgical technique while performing cardiac surgery to minimize the risk of aneurysm formation.